Home Intelligent Based on Privacy Camera and Home Alarming Systems - Pavinee Kijudomsin; Chavana Pavaganun; Somkuan Kaviya; Waraporn Nacharee; Preecha P. Yupapin (My University, 2011)
Attempts on the introduction of systems of the e-JIKEI Network, a novel concept on operating security camera system, are reviewed. The concept of the e-JIKEI network is that a community will have a strong ability to prevent crime only if some residents keep watch their surroundings. Added up with the intelligent home alarming system based on wireless sensor network is to promote greater home security.
Keywords: Security system; Home security; Trade Secret Protection Methods